Spontaneous Rupture of Renal Cell Carcinoma in Pregnancy, Surgical Management With Fetal Preservation:A Case Report - Hassanpour, Abbas; Ahmed, Faisal; Shirazi Yeganeh, Babak; Namavar Jahromi, Bahia; Makarem, Alireza (Urology Journal, 2018)
Spontaneous Retroperitoneal hemorrhage in pregnancy is a rare condition. Renal angiomyolipoma (RA) is the most common cause of this hemorrhage. To the best of our knowledge, this is the first reported case of Wunderlich syndrome (WS) due to renal cell carcinoma (RCC) diagnosed in the second trimester of pregnancy.